Relationship between lipoprotein (a) and subclinical carotid atherosclerosis in asymptomatic individuals - França, Victor; Gomes, Érica Ivana Lázaro; Campos, Edite Vieira Silva de; Zago, Vanessa Helena de Souza; Nunes, Valéria Sutti; Faria, Eliana Cotta de (Clinics, 2022)
Background: This study aimed to evaluate the associations between Lipoprotein (a) ‒ Lp(a) levels and carotid Intima-Media Thickness (cIMT) and with carotid plaques in healthy subjects because of previous contradictory data. Methods: A total of 317 healthy normolipidemic subjects (20‒77 years old) were selected. The cIMT and atherosclerotic plaques were determined by B-mode ultrasonography. Mann-Whitney tests were performed to compare the groups according to Lp(a) levels and to explore the associations between Lp(a), carotid plaques, and cIMT, logistic and linear regression analyses were performed. Results: Studied population (51% females, median age 43 years old) presented carotid plaques and cIMT ≥ 0.9 mm in 23% and 18% of the participants, respectively. The group with Lp(a) levels > 30 mg/dL presented significantly higher age and atherosclerotic plaques. Indeed, multivariate linear regression analysis showed a significant association between Lp(a), age, and race. On the other hand, logistic regression analysis demonstrated that the subjects with Lp(a) > 30 mg/dL have a significantly high risk of carotid plaques. Conclusion: The data from the present study indicate that Lp(a) levels above 30 mg/dL contribute to the development of carotid plaques even in apparently healthy participants.